Hubungan Kesiapan Belajar dengan Hasil Belajar Matematika Kelas IV SDN 013 Sukamaju Kecamatan Singingi Hilir - Eka Kumalah Sari; Siti Quratul Ain (Civiliza Publishing, 2022)
Readiness to learn will affect the learning outcomes obtained by students. But the fact is that not all grade IV learning outcomes at SDN 013 Sukamaju, Singingi Hilir District, who have good learning readiness, finally get good Mathematics learning outcomes. So that it raises the question of whether there is a significant relationship between learning readiness and learning outcomes for fourth grade Mathematics at SDN 013 Sukamaju, Singingi Hilir District. This study aims to determine whether or not there is a significant relationship between learning readiness and mathematics learning outcomes for grade IV SDN 013 Sukamaju, Singingi Hilir District. This research is a descriptive quantitative research. The data collection technique used was in the form of a questionnaire/questionnaire given by 56 respondents containing statements or questions to be answered by students whose contents were students' readiness to learn Mathematics for grade IV SDN 013 Sukamaju, Singingi Hilir District and documentation of learning outcomes. Determination of the sample in this study using a saturated sample technique because all members of the population are used as samples in this study. Data analysis was carried out using the help of computer calculations with SPSS version 24 for windows. The results showed that there was a significant relationship between learning readiness and mathematics learning outcomes for Grade IV SDN 013 Sukamaju, Singingi Hilir District. In addition, the development of readiness is the most influential indicator of learning outcomes.